Eye Care in Four Decades in Nepal - Pokhrel, Ram Prasad (Nepalese Journal of Ophthalmology, 2018)
The Eye Care in Nepal was in rudimentary state till 1971 with the number of cataract surgery being less than 500 cases per year including the mobile Eye camps. The Bir hospital was the only eye hospital at that period, however, it was without slit lamp nor operating microscope and the waiting list of bilateral cataract was more than one year. Those elderly people who came with bilateral cataract with a big hope could not be operated due to less number of eye beds and operation theater. Prof Ram Prasad Pokhrael visited various mobile eye camps in remote hills and saw the tremendous problem of blindness. With a lot of struggle of creating awareness amongst the public for the need of eye hospital and with the support from few stakeholders, Nepal Eye Hospital was created in 1974.